PSVI-19 Evaluation of birth weight, weaning weight and average daily weight gain of Holstein female calves carrying the SLICK1 allele of the Prolactin Receptor (PRLR) gene. (8th October 2021) - Carmickle, Allie T; Zamaroni, Madison R; Pereira, Jessica; Hansen, Peter J; Denicol, Anna C
Abstract: Objectives of this study were to evaluate birth weight (BW), weaning weight (WW), and average daily weight gain (ADG) of female calves carrying the SLICK1 allele, i.e., the slick gene. Holstein cows in four dairy farms located in central California were inseminated with semen from two heterozygous slick Holstein sires to produce slick and non-slick calves. Calves were born during the cool season (November 2019-March 2020). BW was recorded for 125 calves in four farms within 24 h of birth; WW was recorded for 92 calves in three farms within one week of weaning. Weaning age was recorded at day of weighing. ADG was calculated as the weight difference between birth and weaning divided by days of age at weaning. Only female calves were used in the analysis. Statistical analyses were performed using the GLIMMIX procedure of SAS version 9.4. The model for BW included the effects of genotype, farm, sire, and the interaction between genotype and farm. The model for WW and ADG included the effects of BW, genotype, farm, weaning age, sire, and interaction between genotype and farm. Significant effects were considered as those with P < 0.05. There was no difference in BW or WW between genotypes (BW: slick=40.1 ± 0.7 vs non-slick=39.7 ± 0.6 kg; P = 0.7 and WW: slick=82.5 ± 2.8 vs non-slick=80.9 ± 2.8 kg; P = 0.6). The mean age at weaning was 64.8 ± 0.4 and was similar for both genotype groups (P = 0.8). As a result, ADG was similar between genotypes (P = 0.7). There was a main effect of farm on BW, WW and ADG. Results indicate that slick heifer calves born in the cool season perform similarly to non-slick calves in regards to birth weight, average daily weight gain, and weaning weight. Funding provided by the Holstein Association USA Research Program and L.E. "Red" Larson Endowment.